Exploring and identifying youth and adult partnerships, the lived experiences and the knowledge and practices of youth development by youth and adult leaders within the American Hereford Association - Tweeten, Jaclyn Faye (Kansas State University, 2023)
Positive youth development (PYD) is a concept that is based around finding the strengths of adolescents driving from the developmental systems theory (PYD) (Lerner et al., 2005a). The Developmental Systems Theory demonstrates that as a person interacts with their current context it enhances their development (Hamilton et al., 2013). In addition to the Developmental Systems Theory positive youth development is also grounded in the Ecological Systems Theory. The Ecological Systems Theory suggests that the development of an individual is based on their interactions in and across the context (Deurden et al., 2010). Youth and adult partnerships are an important part of a youth’s environment and can influence their development (Zeldin et al., 2008). To better understand the perceptions and interaction of the development of young people this study utilized Jones (2004) Involvement and Interaction Rating scale which analyzes youth and adult interactions while working together in community-based programs. Allport’s (1954), Intergroup Contact Theory was used as a theoretical framework which argues that by bringing people together in group settings, prejudices and biases will be reduced, specifically those that have less power, privilege, and status. In the context of this study, prejudice refers to stereotypes such as age, gender, attitudes, personalities, perceptions, and preferences towards an individual. In addition to Intergroup Contact Theory this study also utilized the Relational Leadership Theory. Relational leadership Theory recognizes that leadership is not just constricted to a single set of leaders or an individual (Uhl-Bien, 2006). Relational Leadership Theory is the study of the dynamics of relationships and the social interactions that occur within an organization or a group and sees leadership as the process in which roles and relationships change within an organization (Uhl-Bien, 2006). Both intergroup contact theory and the relational leadership theory were useful for this study because it assessed the relations that people have with each other such as youth and adult partnerships. When groups interact, mutual learning is created as people come together for a common purpose creating strong positive relationships. When groups interact and create mutual learning, cooperation among each other, and have an equal status within a group, positive youth development can occur (Jones, 2004). There is limited research that exists on PYD in a trade industry; this study focused on youth and adult interactions within the American Hereford Association (AHA) and how these interactions impact the development of young people. Understanding the lived experiences of the youth and adult leaders in the AHA will allow researchers to offer recommendations to help the AHA better serve their members. The target population for this research study consisted of previous and current junior board members, previous ambassadors, volunteers, and staff within the AHA. The design of this study is a mixed methods study, specifically an explanatory sequential design (Toyon, 2021). Mixed methods approach to research combines both qualitative and quantitative data collection into one study (Molina-Azorin, 2012). Using both quantitative and qualitative methods, the results of this study indicated that participants were overall positive in their interactions with each other, specifically youth and adult interactions. Statistically significant differences were found on youth and adults’ perceptions of the statement “adults are considerate of youth opinions” with adults being more positive than youth in their overall perceptions. In addition, “youth make their own decisions” was statistically significant by youth leaders with junior board members rating their perceptions slightly higher than ambassadors. Qualitative results revealed that youth and adults felt comfortable working together and that youth believed that their voice was heard. However, there were some discrepancies in what it means to be heard as many youths felt that the adult listened to them but did not actually hear them because their ideas were not used for the event. Additionally, almost all participants did not fully understand what positive youth development is. As this research has implications for youth and adult relationships and those that work with young people, several recommendations emerged. One of these recommendations is that adults should continue to interact positively with the youth leaders of the organization. This also includes asking the youth for their opinions which may change the youths’ perceptions on what it means to be heard. It is recommended that a training occur so that all people involved in the AHA understand positive youth development concepts when working with youth. Future research is needed to determine if perceptions and thoughts change after the implementation of a training as this research was limited to only those in leadership positions in the year 2019-2023. Research to gauge youth and adults’ understanding of positive youth development and concepts after a PYD training would help determine the impact of the training and their knowledge of PYD.
Keywords: Positive youth development; Youth and adult partnership; Trade industry; Developmental relationships; Youth and adult leadership